The Study Of Appeal Principles On Kobushi (2012) - Low, Cin Hwa (2021)
With the ever increasing demand in visual quality and details in animation, expectation for animation. In order to increase the quality of an animation,appeal is one of the factor that would attract Appeal principles is the essence in the principle of animation, a guideline for novice and experienced animator for producing a sucessful and believable animation. Famous animation production studio such as Inspedia has work with company from overseas such as Xilam, Zagtoon, Cartoon and other famous international animation studios. Inspedia has cooperate with other company and produced many famous animation series such as Zig and Sharko, Combo Ninos and one of them including Kobushi. Kobushi is a Japanese themed French animation, which make it has a unique appeal that attract audience to watch the animation. A deeper research are needed in order to find out more about the appeal of Kobushi and the general audience opinion on Kobushi’s appeal.The aim of the research is to study the appeal principles apply on Kobushi (2012), a 2D animated TV series premiered on Gulli. The reference points here are conference paper and thesis paper regarding the the principles of animation and the appeal principles of appeal. The research method which use in the research are quantitative and qualitative method. The approach such as survey, content analysis will be taken in order to collect numerous data on how appeal principles has relation with the appeal of Kobushi. Researcher are expect to find positive response from audience from the distribute because Kobushi’s character design and theme are all-aged friendly and unique. This research was able to help researcher in developing a character and creating a believable animation. Thus,the result of the research would expect to benefit novice animator and experience animator alike in order to deepen the understanding of appeal of an animation.